Putative Role Of Fgf 23 In The Development Of Hypophosphatemia And Bone Fructures In An Anemic Patient Treated By Intravenous Saccharated Ferric Oxide - Risa Ishida; Shohei Nakanishi; Sachie Hisose; Jong Il Kim (The Korean Society of Nephrology, 2012)
A post-menopausal patient with normal kidney function was referred to our hospital because of severe lumber pain. She had been treated by initially oral, and then by intravenous iron for longer than five years for the treatment of iron deficiency anemia due to recurrent GI bleeding. On admission, multiple lumber bone fracture with low bone mineral density was confirmed. Laboratory tests revealed severe hypophosphatemia (1.6 mg/dl) with slight decrease of calcium ion level. Serum levels of 25D and 1,25D were low normal, while increase of intact PTH (83.9 pg/ml) and FGF23 (60 pg/ml) were observed. After terminating intravenous iron supplement, her symptoms and hypophsophatemia were gradually normalized with oral active vitamin D treatment. Although we could not completely exclude the contribution of disturbed iron absorption from the intestine, damages of proximal tubular cells by iron, and osteomalacia caused by the deposition of iron, increased FGF23 level may have played critical roles in the development of severe hypophosphatemia in this patient. Such hypophosphatemia due to high FGF23 has recently been reported in patients treated by intravenous sacharated ferric oxide.